Nutrition for the young athlete - Meyer, F.; O'Connor, H.; Shirreffs, S. M. (Journal of Sports Sciences, 2007)
Athletics is a popular sport among young people. To maintain health and optimize growth and athletic performance, young athletes need to consume an appropriate diet. Unfortunately, the dietary intake of many young athletes follows population trends rather than public health or sports nutrition recommendations. To optimize performance in some disciplines, young athletes may strive to achieve a lower body weight or body fat content and this may increase their risk for delayed growth and maturation, amenorrhoea, reduced bone density, and eating disorders. Although many of the sports nutrition principles identified for adults are similar to those for young athletes, there are some important differences. These include a higher metabolic cost of locomotion and preferential fat oxidation in young athletes during exercise. Young athletes, particularity children, are at a thermoregulatory disadvantage due to a higher surface area to weight ratio, a slower acclimatization, and lower sweating rate. An appropriate dietary intake rather than use of supplements (except when clinically indicated) is recommended to ensure young athletes participate fully and safely in athletics.